Characteristics of fiber laser weldments of two phases (α+β) titanium alloy. (October 2018) - Kumar, Chandan; Das, Manas; Paul, C.P.; Bindra, K.S.
Highlights: 2 mm thick Ti-6Al-4 V alloy sheet is successfully welded using fiber laser. Cracks are not found in the weldments at all welding conditions. Variation in α´ martensite is observed within heat affected zone. Various morphologies of α´ martensite are observed in fusion zone. Fusion zone hardness and tensile strength increase with increased welding speed. Abstract: Laser welding experiments are conducted at various welding conditions on Ti-6Al-4 V alloy plates by employing fiber laser. A special type of workpiece fixture having provision of supplying shielding gas is fabricated for the protection of weld bead efficiently from environmental contamination. The influence of process parameters i.e. welding speed on the development of non-homogeneous microstructure of the weld bead is investigated by conducting microstructural characterization in details. Different morphologies of martensitic phase such as α´martensite, massive αm, blocky α and basket-weave structure are observed in the fusion zone. The variation in amount of α´ martensite is observed within heat affected zone. The calculated cooling rate and microstructure evaluation in the fusion zone are consistent with the continuous cooling transformation curve of Ti-6Al-4 V alloy. Higher hardness is found in fusion zone of the weldments. At lower welding speeds (500 ̶ 600 mm/min), underfill weld defects and at higher welding speed (800 mm/min) the micro-pores are observed in the weld bead. However, sizes of micro-pores are within the acceptable range as per BSEN: 4678 European standard. The microhardness and tensile strength of weldments are increased with increasing welding speed due to the development of finer α´ martensite in the fusion zone. For a fixed beam power of 1200 W, the most favorable range of welding speed (700 ̶ 800 mm/min) is identified which produced consistently high quality welds without crack and acceptable pore size. Vickers microhardness and tensile test results indicate that the optimal process parameters obtained in the current study can be suitably used in industries.